BIBLIOMETRIC MAPPING OF ECONOMIC EDUCATION: BRADFORD’S LAW, CO-OCCURRENCE NETWORK ANALYSIS, AND THEMATIC MAPPING - Martha, Jefry Aulia; Wardoyo, Cipto; Hermawan, Agus (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
Economic education, as one of the fields of study in higher education, plays a crucial role in preparing the younger generation to understand and manage economic decisions. Research in this field has been growing rapidly, yet the direction of research needs to be well-mapped to identify future gaps. This study employs bibliometric techniques, including Bradford’s Law, Co-occurrence Network Analysis, and Thematic Mapping. The results reveal that the distribution of publications in this field is highly uneven. Bradford’s Law analysis shows that most publications come from a small number of key journals, while co-occurrence analysis identifies strong connections between various themes in economic education, with